MultiBac complexomics. (August 2012) - Trowitzsch, Simon; Palmberger, Dieter; Fitzgerald, Daniel; Takagi, Yuichiro; Berger, Imre
Recombinant production of multiprotein complexes is an emerging focus in academic and pharmaceutical research and is expected to play a key role in addressing complex biological questions in health and disease. Here we describe MultiBac, a state-of-the-art eukaryotic expression technology utilizing an engineered baculovirus to infect insect cells. The robust and flexible concept of MultiBac allows for simultaneous expression of multiple proteins in a single cell, which can be used to produce protein complexes and to recapitulate metabolic pathways. The MultiBac system has been set up as an open-access platform technology at the European Molecular Biology Laboratory (EMBL) in Grenoble, France. The performance of this platform and its access modalities to the scientific community are detailed in this article. The MultiBac system has been instrumental for unlocking the function of a number of essential multiprotein complexes and recent examples are discussed. This article presents a novel concept for the customized production of glycosylated protein targets using SweetBac, a modified MultiBac vector system. Finally, this article outlines how MultiBac may further develop in the future to serve applications in both academic and industrial research and development.